Intercultural Public Relations Realities and Reflections in Practical Contexts - Ni, Lan; Schlupp, Qi Wang; Sha, Bey-Ling (New York Routledge, 2022)
This book continues the groundbreaking work begun in Intercultural Public Relations: Theories for Managing Relationships and Conflicts with Strategic Publics (Routledge, 2018), by applying the theoretical framework of intercultural public relations to actual practice.

Practical public relations contexts examined by the contributing chapter authors—both scholars and practitioners—include corporations, government, military, healthcare, education, and activism. The book covers real-world situations, including the training of practitioners to become more interculturally competent, identifying and understanding publics or stakeholders with different cultural backgrounds and identities, building and maintaining relationships with these publics/stakeholders, and managing conflicts with them.

Offering practical guidance while examining both best practices and difficult challenges, this book is useful for public relations researchers, practitioners, and students as they explore how intercultural public relations contributes to organizational effectiveness and social change.
A Theoretical Framework of Intercultural Public Relations / Lan Ni --Pinpointing, Prioritizing, and Practicing Purpose / Alexis Fitzsimmons, Eve Heffron, Yufan Sunny Qin, and Marcia W. DiStaso -- Unpacking the Meat Industry’s COVID-19 Response / Kirsten Theye and Najla Ghazi Amundson -- Building Relationship with the Public from Different Cultural Backgrounds on Social Media: A Case Study on Estée Lauder’s Social Media Communication Strategies in the United States and China / Yaqi Hu, Wenze Lu, and Cindy Sing Bik Ngai -- When Black College Presidents Visit the White House:The Case of a Culture Clash in Crisis Management / George Daniels and Keonte Coleman -- Enhancing the Global Mindset in Military Public Affairs / Karen Naumann and Oshawn Jefferson -- The Implications of Public Health Messaging Strategies: How Branding Disease May Improve Public Health Awareness in the Gulf Cooperation Council (GCC) / Mariam F. Alkazemi, Nouf B. Alkhubaizi, and Joshua J. Smith -- Managing a Relational Triad during COVID-19: Strategic Management, Intercultural Competency, and Negotiation Savvy / Ann D. Summerall-Jabro -- Exploring an Integrated Approach to Understanding and Communicating with Publics for Activist Organizations: Black Liberation Movement / LaRahia Smith and Lan Ni -- Intercultural Communication Competence in the Moral Circle: Learning from Research and Practice / Qi Wang Schlupp -- Conclusion / Qi Wang Schlupp, Lan Ni, and Bey-Ling Sha.
Includes bibliographical references and index
Keywords: Public relations; Intercultural communication